Birth cohort effects on adolescent alcohol use: The influence of social norms from 1976-2007 - Keyes, Katherine M. (2012)
CONTEXT: The substantial changes adolescent alcohol use prevalence over time suggests that population-level environmental factors are important determinants of use, yet the potential influence of such environmental factors is inadequately understood. OBJECTIVE: The present study investigated whether adolescents in birth cohorts and/or time periods characterized by restrictive social norms towards alcohol were at decreased risk for alcohol use and binge drinking, controlling for individual attitudes (disapproval) towards use. DESIGN: Aggregated data from thirty-two annual national surveys of U.S. high school students. PARTICIPANTS: A total of 1,032,052 students contributed data from 1976 through 2007. EXPOSURE: The social norm was measured by creating scores for each time period and birth cohort indicating the proportion disapproving of weekend binge drinking. OUTCOMES: Frequency of past-year alcohol use and any instance of binge drinking (5+ drinks) in the past two-weeks, analyzed using multi-level models clustering individuals within time periods and birth cohorts. Period- and cohort-specific social norm scores were modeled as predictors, controlling for individual attitudes and demographics. RESULTS: Individuals who matured in birth cohorts with more restrictive social norms were less likely to use alcohol compared to individuals who matured in cohorts with more permissive norms; each 5% increase in the cohort-specific disapproval was associated with a 12% decrease in the odds of past-year alcohol use (OR=0.88, 99% C.I. 0.87-0.89). The effects of cohort-specific disapproval were notably stronger among White than non-White adolescents. CONCLUSIONS: The present study documents the importance of considering time-varying population-level risk factors in the study of adolescent alcohol use, and indicates that even after an individual’s personal attitudes are accounted for, risk is shaped by cohort effects whereby the norms within the cohort contribute to the risk of adolescent alcohol use.